Smart Wall Clock / Nurul Amierah Noor Amran - Noor Amran, Nurul Amierah (2020)
Smart wall clock has many advantages compared to others normal wall clock because we develop some new features which very functioning that have their own application and code, thermal camera, allow to set reminders, background and theme of the clock. Our product has great quality and technology that can give satisfaction to the consumers. We applied some features which could help people who are busy with their work and must take care of their children. Therefore, with our product, it could minimize their difficulty to handle both at the same time. Furthermore, we provide the affordable price with high quality material and long-lasting product. We develop this product in order to overcome the problem from previous issue that happen for wall clock user especially household population. By this product development, they do not have to worry about the upcoming problem because we present a great function that will give more benefit to the consumers. Normally, the population that will assess our product is household. They usually use wall clock which is it is important for them to monitor time. However, by using our product which is smart wall clock, it will make them easy to monitor time and will more advanced with new features we presented. Our smart wall clock with the affordable price would attract both gender male and female because it is come with various of design that suitable for both genders. Therefore, the target population were change to Malaysia citizen with the range age between 25 – 54 and 54 – 64 years old. The competitors, the Glance team is based in Singapore and is marketing the company as the first smart wall clock that displays data from wearables including Jawbone and Fitbit, smart home devices like SmartThings, Nest and more. With key management that consist of general manager, HR manager, operation manager, finance manager and marketing manager, we able to control our company.